A new map of the chanonry of the cathedral church of the Holy and Undivided Trinity at Elgin, Morayshire. (May 2022) - Firth, David
Abstract : In the Victorian Era, several Morayshire antiquaries attempted to reconstruct the plan of the ancient precincts, or chanonry, of the cathedral church of the Holy Trinity at Elgin. So comprehensive was their work, and such were their reputations, that little has been done since to re-examine their legacy. A discovery in the library of the University of Aberdeen has led to a review of the work that has previously been accepted as showing the layout of the cathedral precincts. It has necessitated the production of a definitive list of the prebends of the cathedral and has provided information regarding some of the chaplainries that were within it. A modified map of the chanonry has been produced based on a previous version which was published by Charles Rampini.